A Web 2.0-based collaborative learning to promote the practices of Islam as a way of life - Ataie, Fariba; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2019)
The research aimed to design, develop and evaluate an innovative Web 2.0-based collaborative learning (CL) under the guidelines of design science research methodology (DSRM). The Islamic ethical system based on verses of the Quran and social constructionist theory as knowledge base, supports the design process. This is in response to the lesser amount of focus on the practical research methods in Islamic education. The developed information Technology artifact was used for two courses in IIUM. The findings of research show that the practical methodology of this study could provide opportunities for practical methodology of this study could provide opportunities for practice of Islam as a way of life or " Islamicisation". In addition, this study's ethical CL process in a social constructionist environment could promote critical thinking, use of knowledge and religious awareness of studnets that are the main goals of IIUM with Islamic education.